Client-Side vs Server-Side Rendering: Impacts on Performance and User Experience in Web Applications - Clapton, Joey; Bastos, Hugo; Batisteli, João Pedro Oliveira; Seufitelli, Danilo Boechat; Tavares, Cleiton (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2025: Anais do XXIV Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2025.15078, 2025)
The increasing complexity of web applications necessitates careful selection of rendering strategies to ensure optimal performance and user experience. This study presents a comparative analysis of Client-Side Rendering (CSR) and Server-Side Rendering (SSR) techniques, evaluating their impact on web application quality based on Google’s Core Web Vitals metrics (CWV). In this work, photo gallery web applications were implemented using both rendering approaches to allow a homogeneous environment for comparable results. Through controlled experiments across five data sizes (ranging from 498 kB to 26 MB), measurements were taken for key performance indicators, including First Contentful Paint (FCP), Speed Index (SI), Time to Interactive (TTI), Largest Contentful Paint (LCP), and JavaScript Heap Used. Statistical analysis using the Kruskal-Wallis test revealed significant performance differences (𝑝 ≤ 0.05) in all metrics. Results show that SSR achieves superior performance in TTI (mean reduction of 62.3%) and LCP (mean reduction of 58.7%), particularly under increased data loads, while CSR exhibits better FCP and SI performance for smaller datasets. The results suggest that the choice between CSR and SSR should consider the application’s specific objectives and usage environment. These findings contribute to evidence-based decision-making frameworks for web application architecture, supporting software quality engineering practices in modern development environments.